2007
DOI: 10.1016/j.jtcvs.2007.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Critical left ventricular outflow tract obstruction: The disproportionate impact of biventricular repair in borderline cases

Abstract: Inappropriate pursuit of biventricular repair in borderline candidates is more frequent and more consequential in survival terms than is inappropriate pursuit of univentricular repair. Use of the univentricular survival advantage tool will help identify infants for whom univentricular repair may be a better choice than attempting biventricular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
154
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 25 publications
3
154
0
Order By: Relevance
“…In a comprehensive review Corno identified risk factors such as quantitative measurements of left ventricular enddiastolic dimensions, aortic and mitral valve orifices indexed for body surface area (Corno, 2005). Associated abnormalities such as younger age, endocardial fibroelastosis, non-compaction of the left ventricle, aortic coarctation, mitral valve abnormalities and pulmonary hypertension are also important risk factors to be considered (Hickey et al, 2007). In the end, both objective measurements and clinical judgment need to be taken into account when deciding what is considered a borderline left ventricle.…”
Section: Background Of Borderline Left Ventriclementioning
confidence: 99%
See 4 more Smart Citations
“…In a comprehensive review Corno identified risk factors such as quantitative measurements of left ventricular enddiastolic dimensions, aortic and mitral valve orifices indexed for body surface area (Corno, 2005). Associated abnormalities such as younger age, endocardial fibroelastosis, non-compaction of the left ventricle, aortic coarctation, mitral valve abnormalities and pulmonary hypertension are also important risk factors to be considered (Hickey et al, 2007). In the end, both objective measurements and clinical judgment need to be taken into account when deciding what is considered a borderline left ventricle.…”
Section: Background Of Borderline Left Ventriclementioning
confidence: 99%
“…However, in true borderline cases, this early decision proves to be difficult due to lack of guidelines with clear -cut predictability. Several scoring systems such as the Rhodes score (Rhodes et al, 1991), Colan score (Colan et al, 2006) and the Univentricular Repair Survival Advantage Tool (Hickey et al, 2007) exist to predict the optimal type of repair. These scoring systems use several left ventricular parameters in an equation, the result of which above or below a given cut-off value generates the predicted most favourable treatment strategy.…”
Section: Decision Making In the Neonatal Phasementioning
confidence: 99%
See 3 more Smart Citations